Kinetics of the Catalytic Desorption of CO2 from Monoethanolamine (MEA) and Monoethanolamine and Methyldiethanolamine (MEA-MDEA). (July 2017) - Akachuku, Ananda; Osei, Anima; Decardi-Nelson, Benjamin; Srisang, Wayuta; Pouryousefi, Fatima; Ibrahim, Hussameldin; Idem, Raphael
Abstract: The kinetics of the desorption of CO2 from CO2 -loaded aqueous single 5 M monoethanolamine and blended 5 M/2 M monoethanolamine-methyldiethanolamine solvents were studied over solid acid γ-Al2 O3 and HZSM-5 catalysts at three desorber temperatures (348, 358 and 368K) at CO2 loading ranging from ∼0.279-0.5 mol/mol for different ratios of catalyst weight/flow rate of amine (W/FAo ) using a bench-scale complete absorber–desorber CO2 capture pilot plant of 2-inch internal diameter and 3.5 ft total height. The kinetic performance, in terms of CO2 produced, activation energy and rate constants, showed that HZSM-5 catalyst provided faster kinetics, higher CO2 produced and lower activation energy than with γ-Al2 O3 .